Educommucation, Communicative Competence and rule of law: education for the of social networks - Alessandro Rezende da Silva (2024)
The study was aimed at a focus group of 10 years old students who studied at a public school in the Federal District, in 2018. Starting from the question: how does the public institution educate its students to use virtual communication? In this way, the objective is to discuss the right to communication in a state of law formed by a traditional hierarchical bureaucracy. The Federal District has an estimated population of 2 million inhabitants, divided into 31 satellite cities. The action research method was used, with interview techniques, data analysis on students actions on social networks, with observation on the techniques-economic paradigm that criticizes new commitments to the information society. Information and knowledge are indispensable for any activity within organizations and, therefore, it is necessary to remove the utopian exaggerations that constitute “computopia”.